2012
DOI: 10.1007/s10834-012-9304-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Money Arguments in Marriage

Abstract: Despite the paucity of empirical evidence indicating the impact of money arguments on spousal relationship outcomes, it is common belief that money plays a large role in the life of couples.This study used panel data from the 1979 National Longitudinal Study of Youth (NLSY79) to examine how money-related arguments affect the marital relationship. Economic theory indicates that initial expectations about the marriage and variance in expectations are both important in predicting relationship satisfaction and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…Because financial conflict may erode relationship satisfaction Britt et al, 2008;Britt & Huston, 2012;Diamond & Hicks, 2011;Kerkmann et al, 2000), we focused on identifying financial factors that might influence relationship satisfaction. Our analyses showed that perceived financial mutuality exerted the greatest influence on relationship satisfaction.…”
Section: The Power Of Perceived Financial Mutualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because financial conflict may erode relationship satisfaction Britt et al, 2008;Britt & Huston, 2012;Diamond & Hicks, 2011;Kerkmann et al, 2000), we focused on identifying financial factors that might influence relationship satisfaction. Our analyses showed that perceived financial mutuality exerted the greatest influence on relationship satisfaction.…”
Section: The Power Of Perceived Financial Mutualitymentioning
confidence: 99%
“…A critical component of continuing relationship satisfaction among adult couples is the sharing of financial values and discussions about important financial issues (Archuleta, 2013;Britt & Huston, 2012;Kerkmann, Lee, Lown, & Allgood, 2000). In turn, higher relationship satisfaction contributes to the overall well-being of individuals, couples and families (Amato & Rogers, 1997;Dyrdal, Roysamb, Nes, & Vitterso, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a majority of college students (90%) who did not have the financial resources to get involved in the same activities as their friends reported feeling financial stress, thus impacting their overall relationship with friends (e.g., less time spent together; Heckman et al, 2014). According to Britt and Huston (2012), college students who had greater perceptions of personal mastery and higher net worth reported feeling less stressed about their financial situations.…”
Section: Transitionsmentioning
confidence: 99%
“…For example, Halliday-Hardie and Lucas (2010) found a direct negative effect of financial stress on relationship satisfaction. Britt and Huston (2012) stated that couples who argue over money are couples who have not taken the time to focus on each other. This is typically during the early stages of their relationship-an opportune time to build on their commitment as a couple.…”
Section: Introductionmentioning
confidence: 99%
“…Differing expectations about fair distributions of resources are a common source of individual stress, and couple conflict in stepfamilies (Gold 2009;. Arguments over money have been found to reduce relationship satisfaction and increase the likelihood of divorce (Britt and Huston 2012), so supporting stepfamilies to work through the complexities of their financial situations and potentially differing expectations may benefit these families (Lown and Dolan 1988). One study found that only 20 % of stepfamily couples had discussed financial management prior to marriage (Coleman and Ganong 1989).…”
Section: Implications For Policy and Practicementioning
confidence: 99%